Light Rapid Transit (LRT) Transport Integration Performance (Case Study on LRT South Sumatra in 2019-2021) - Komalasari, Yeti (Graduate Program Magister Manajemen Pendidikan, 2022)
The purpose of this research is to describe and analyze the performance of the Light Rapid Transit (LRT) transportation integration, the South Sumatra LRT case study and the need for mode integration in realizing multimodal transportation. The research method uses the constructivism paradigm through qualitative research approaches and types with data collection techniques through observation, interviews and documentation. The main finding in this study is that the realization of passengers who integrate has decreased significantly due to the covid -19 pandemic with travel restrictions, although not as much as in early 2020 in 2021, passengers who integrate have increased. In 2019 the stations with the most passenger integration were at DJKA and Bumi Sriwijaya stations, in 2020 the most were at DJKA and Ampera stations, while in 2021 the most were at DJKA and Ampera stations. The novelty/originality in this research is supported by the latest observational data and studies that support the integration of Light Rapid Transit (LRT) in realizing the principle of multimodal transportation in South Sumatra.